Slow Art - Visser, Mattijs; Museum Kunst Palast, Düsseldorf (Düsseldorf : Museum Kunst Palast Düsseldorf, 2005)
Baerveldt, Erzsébet ; Borremans, Michaël ; Braeckman, Dirk ; Claerbout, David ; Davids, Yael ; De Bruyckere, Berlinde ; de Cordier, Thierry ; Delvoye, Wim ; Devriendt, Robert ; Dijkstra, Rineke ; Dolron, Désirée ; Dumas, Marlene ; Fabre, Jan ; François, Michel ; Goudzwaard, Kees ; Höller, Carsten ; Johannesma, Rob ; Koster, Jan ; Kraijer, Juul ; Manders, Mark ; Mik, Aernout ; Mistiaen, Carlo ; Neus, Elske ; Peeters, Antoniëtta ; Provily, Philip ; Raedecker, Michael ; Roosen, Maria ; Schoorel, Maaike ; Strik, Berend ; Tuymans, Luc ; Van Caeckenbergh, Patrick ; van Elk, Ger ; Van Imschoot, Jan ; Van Lankveld, Rezi ; Vanmechelen, Koen ; Wertheim, C.A. ; Wright, Cindy ; Zwakman, Edwin
Biog. per kunstenaar
Publikation anlässlich der Ausstellung 'Slow Art' im Museum Kunst Palast in Düsseldorf, 16.07.2005-07.11.2005
boek